Factors associated with Chlamydia trachomatis and Neisseria gonorrhoeae infection among female sex workers in Nagaland, India - Medhi, Gajendra K.; Mahanta, Jagadish; Phukan, Sanjib K.; Paranjape, Ramesh S.; Kermode, Michelle; Goswami, Prabuddhagopal (International Journal Of Community Medicine And Public Health, 2017)
Background: There is limited knowledge on the prevalence and correlates of sexually transmitted infections (STI) among women practicing sex work in the high HIV prevalence settings of northeast India, especially in Nagaland. We assessed the prevalence and risk factors of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) among female sex workers (FSW) in Dimapur, Nagaland. Methods: 417 FSWs were recruited into this cross–sectional study using Respondent Driven Sampling (RDS) in 2009. Information on socio-demographic characteristics, sexual risk behaviours and exposure to prevention interventions were collected from them and urine samples were tested for NG and CT. Multivariate logistic regression analysis was performed to assess the factors associated with NG and CT. Results: The RDS-adjusted prevalence of HIV, NG and CT was 11.4%, 6.6% and 19.5% respectively. The reported condom use with clients and regular sex partners were only 29.1% and 9.6% respectively. Being in the sex trade within the last 2 years was independently associated with greater risk for NG and CT. Having more than 5 clients was independently associated with greater likelihood for CT and seropositivity for HIV was independently associated with NG. Conclusions: High prevalence of NG/CT was documented among FSWs with relatively new entrants into sex trade having the highest risk. The combination of high STI prevalence and low consistent condom use is likely to contribute to an escalating HIV epidemic in this already high HIV prevalence setting. There is need to strengthen public health measures for screening and management of NG and CT among FSWs.